Non-use of cancer information services among people experiencing cancer in Ireland. (February 2020) - Sheridan, A.; Kemple, M.; Hyde, A.; Fox, P.; Furlong, E.; Coughlan, B.; Bell, M.; Naughton, C.; Carberry, S.; Drennan, J.
Abstract: Purpose: The purpose of this study was to explore the reasons for non-use of a national cancer society's cancer information services among people experiencing cancer. Method: This study used a qualitative design. Semi-structured interviews were conducted with a total of 17 participants who had not previously utilised the Cancer Society's information services. Data were analysed using Thematic Analysis. Results: The key themes to emerge from the date were 'living in the here and now' and 'awareness of the Cancer Society'. For most participants, not utilising cancer information services was a means of coping with the initial diagnosis and the impact of treatment. Those who progressed to being ready to seek information identified the multi-disciplinary team as the primary source of trusted information, with particular mention of cancer nurse specialists. For participants with children, their role as a parent was central in how they managed their diagnosis. The majority of participants lacked awareness of the range of services provided by the Cancer Society. Conclusions: Reasons for non-use of cancer information services were identified as: readiness to seek information and a lack of knowledge of the Cancer Societies' services. Cancer information services need to continue make a concerted effort to enhance visibility and awareness of its services to optimise patient engagement. Highlights: Not utilising cancer information services related to participants' way of managing the initial shock of diagnosis and impact of treatment. Information seeking styles appear to be fluid as some participants progressed to being ready to seek and receive information. The multidisciplinary team, particularly cancer nurse specialists, were identified as the primary source of trusted information. The primary barrier to accessing cancer information services was lack of knowledge regarding range of services provided.